2013
DOI: 10.1371/journal.pgen.1003434
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mapping of Spontaneous Mitotic Recombination Hotspots on the 1.1 Mb Arm of Yeast Chromosome IV

Abstract: Although homologous recombination is an important pathway for the repair of double-stranded DNA breaks in mitotically dividing eukaryotic cells, these events can also have negative consequences, such as loss of heterozygosity (LOH) of deleterious mutations. We mapped about 140 spontaneous reciprocal crossovers on the right arm of the yeast chromosome IV using single-nucleotide-polymorphism (SNP) microarrays. Our mapping and subsequent experiments demonstrate that inverted repeats of Ty retrotransposable elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
253
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(281 citation statements)
references
References 58 publications
26
253
2
Order By: Relevance
“…This excision reaction required Exo1 and was stimulated by both a mispair and Msh2-Msh6, where mispair binding by Msh2-Msh6 was required for stimulating excision. Strikingly, the excision tracts observed were very long, as long as 1,750 bp in reactions with the substrate containing a nick at the NaeI site and 2,900 bp with the substrate containing a nick at the AflIII site, which approximates the length of MMR excision tracts predicted from genetic studies of gene conversion (12,53). The electron microscopy experiments indicated that the length of the longest excision tract was threefold longer in the presence of Msh2-Msh6.…”
Section: Discussionmentioning
confidence: 65%
“…This excision reaction required Exo1 and was stimulated by both a mispair and Msh2-Msh6, where mispair binding by Msh2-Msh6 was required for stimulating excision. Strikingly, the excision tracts observed were very long, as long as 1,750 bp in reactions with the substrate containing a nick at the NaeI site and 2,900 bp with the substrate containing a nick at the AflIII site, which approximates the length of MMR excision tracts predicted from genetic studies of gene conversion (12,53). The electron microscopy experiments indicated that the length of the longest excision tract was threefold longer in the presence of Msh2-Msh6.…”
Section: Discussionmentioning
confidence: 65%
“…In our previous studies of spontaneous (22) and UV-induced mitotic recombination events (23), more than half of the crossover-associated gene-conversion events were 4:0 conversions (Fig. 5C) or 3:1/4:0 hybrid events (Fig.…”
Section: Experimental Approach For Mapping Regions Of Loss Of Heterozmentioning
confidence: 70%
“…In diploid strains that are heterozygous for many SNPs, mitotic recombination events between homologous chromosomes can be mapped by identifying regions that have undergone loss of heterozygosity (LOH). Previously, using SNP-specific microarrays (21), we mapped spontaneous recombination events on the right arm of chromosome IV (22), and UV-induced events throughout the genome (23). In our current study, we map unselected mitotic recombination events induced by low levels of DNA polymerase-α throughout the yeast genome, in addition to mapping reciprocal cross-overs selected on chromosomes V and IV.…”
Section: Experimental Approach For Mapping Regions Of Loss Of Heterozmentioning
confidence: 99%
See 2 more Smart Citations